Legal Responsibility of Hospital for Case of Exchange of Baby Identity Reviewed from Legal Certainty (Case of Alleged Exchange of Babies at Cempaka White Islamic Hospital) - Precia Widyatomo; Ina Heliany; Jamiatur Robekha (Jurnal Info Sains : Informatika dan Sains, 2025)
In the process of providing health services, errors or negligence can occur in the form of patient identification errors either in the process of diagnosis, treatment, or other medical procedures. Such negligence or error can potentially result in injury or loss to the patient. The purpose of providing correct patients identification is to identify patients who will be given appropriate services, actions, or treatment. One of the vulnerabilities of services for newborns is the error of health workers in providing identification. Newborn babies must be matched with the mother who gave birth to them, namely immediately attaching an identity bracelet immediately after the baby is born to avoid the baby being exchanged. The formulation of the problems discussed are: 1) How is the mechanism and verification of the identity of babies born in hospitals to prevent cases of baby exchange? and 2) What is the form of legal responsibility of the hospital if there is a case of baby identity exchange according to laws and regulations in the context of legal certainty? The research method used is the normative juridical method, namely the research is conducted with a literature approach, namely by studying books, laws and regulations and other documents related to this research. Based on the results of the study, the author concludes that the legal responsibility of the hospital in the event of a case of a baby's identity being exchanged according to laws and regulations in the context of legal certainty is that the hospital can be held accountable for criminal, civil, state administration, and professional ethics or for negligence that results in losses for patients and families. Referring to the provisions of Article 46 of Law Number 44 of 2009 concerning Hospitals, it states that: the hospital is legally responsible for all losses caused by negligence by health workers in the hospital. In an effort to hold the hospital criminally responsible, it was first started by providing a number of compensation, and/or compensation, of course the hospital must sit down together with the policy makers of the hospital.